The sustainability of the gig economy food delivery system (Deliveroo, UberEATS and Just-Eat): Histories and futures of rebound, lock-in and path dependency. Issue 5 (2nd May 2023) - Lord, Carolynne; Bates, Oliver; Friday, Adrian; McLeod, Fraser; Cherrett, Tom; Martinez-Sykora, Antonio; Oakey, Andy
ABSTRACT: Online food delivery has transformed the last-mile of food and grocery delivery, with unnoticed yet often significant impacts upon the transport and logistics network. This new model of food delivery is not just increasing congestion in urban centers though, it is also changing the contours and qualities of those doing delivery—namely through gig economy work. This new system of food consumption and provision is rapidly gaining traction, but assessments around its current and future sustainability tend to hold separate the notions of social, environmental and economic sustainability—with few to date working to understand how these can interact, influence and be in conflict with one another. This paper seeks to work with this broader understanding of sustainability, whilst also foregrounding the perspectives of gig economy couriers who are often marginalized in such assessments of the online food delivery system. We make use of systems thinking and Campbell's conflict model of sustainability to do this. In assessing the online food delivery in this way, we seek to not only provide a counternarrative to some of these previous assessments, but to also challenge those proposing the use of gig economy couriers as an environmentally sustainable logistics intervention in other areas of last-mile logistics to consider how this might impact the broader sustainability of their system, now and in the future.